Attitudinal Meaning in Kevin Carter’s Suicide Note - Eva Tuckyta Sari Sujatna; Meita Lukitawati Sujatna; Kasno Pamungkas; Nurul Hikmayaty Saefullah (Ranah: Jurnal Kajian Bahasa, 2024)
This study explicates attitudinal meaning in a suicide note based on Systemic Functional Linguistic approach. This research aims to figure out the attitudinal meaning including affect, judgment, and appreciation in Kevin Carter’s suicide note. Kevin Carter was a photojournalist from South Africa who won a Pulitzer Prize in 1993 for a vulture patiently observing a little girl who collapsed in the forefront of hunger photograph who committed suicide in 33 years old. The method applied in this research is a qualitative research method. The data were taken from Kevin Carter’s suicide note, then they were classified based on the three types of attitude elements. The present writers draw the result of the three attitudinal meaning elements, firstly the affects (feeling) found in the Kevin Carter’s suicide note showed the emotions that deal with the negative feelings. Secondly, the judgment or ethics relate to attitude toward habit and behaviour delivered in the Kevin Carter’s suicide note deals with condemn as the negative moral. The last, the appreciation connects to aesthetics which involves the evaluation indicated in the Kevin Carter’s suicide note relates to the reaction which has a process type (affection) as an interpersonal.